The Relationship Among Expressions, Labels, and Descriptions of Contempt. (article). - Matsumoto, David
This article reports 4 studies that demonstrate that the contempt expression is reliably associated with situations that elicit contempt and that the inability to label the contempt expression reflects a problem with its label or concept and not with the relationship between each expressions and emotion . In study 1, the labeling of contempt in fixed -choice judgment tasks did not occur because of a process of elimination. In studies 2 and 3, the contempt expression was associated with situations that elicit contempt , but participants did not label the situations in an open-ended response . In study 3, participants also reliably labeled the contempt expression with situation rather than with labels and did not generate contempt situation from labels. In study 4, participants reported using, hearing, and reading about contempt the least among 7 emotions tested. -- (from the author)
Keywords: Psychology-Periodicals.